2021
DOI: 10.1002/glia.24018
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fibroblast growth factor‐inducible 14 expression transforms proneural‐like gliomas into more aggressive and lethal brain cancer

Abstract: High‐grade gliomas (HGGs) are aggressive, treatment‐resistant, and often fatal human brain cancers. The TNF‐like weak inducer of apoptosis (TWEAK)/fibroblast growth factor‐inducible 14 (Fn14) signaling axis is involved in tissue repair after injury and constitutive signaling has been implicated in the pathogenesis of numerous solid cancers. The Fn14 gene is expressed at low levels in the normal, uninjured brain but is highly expressed in primary isocitrate dehydrogenase wild‐type and recurrent HGGs. Fn14 signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Fn14 upregulation helps to mediate local tissue responses including tissue remodeling and inflammation, for example during burn wound repair (Liu et al , 2019), but also controls proliferation, apoptosis, cell migration, and differentiation (Winkles, 2008; Poveda et al , 2021) and synapse function in the visual system (Cheadle et al , 2020). However, increased Fn14 levels or signaling are also linked to chronic diseases, such as most solid tumor types, acute kidney disease, fibrosis, Alzheimer's disease, and cerebral ischemia (Cheng et al , 2013; Perez et al , 2016; Hu et al , 2017; Wang et al , 2017; Connolly et al , 2021; Nagy et al , 2021). Thus, Fn14 is intensively tested as a drug target using monoclonal antibodies or immunotoxins targeted to Fn14 or fusion proteins encoding Fn14 decoy receptors, which improve pathology in various mouse models of disease, such as for lung tumors, triple‐negative breast cancer, tumor cachexia, and atherosclerosis (Yepes et al , 2005; Schapira et al , 2009; Michaelson et al , 2011; Wajant, 2013; Zhou et al , 2014; Johnston et al , 2015; Peng et al , 2018; Alvarez de Cienfuegos et al , 2020; Dancy et al , 2020; Wolf et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Fn14 upregulation helps to mediate local tissue responses including tissue remodeling and inflammation, for example during burn wound repair (Liu et al , 2019), but also controls proliferation, apoptosis, cell migration, and differentiation (Winkles, 2008; Poveda et al , 2021) and synapse function in the visual system (Cheadle et al , 2020). However, increased Fn14 levels or signaling are also linked to chronic diseases, such as most solid tumor types, acute kidney disease, fibrosis, Alzheimer's disease, and cerebral ischemia (Cheng et al , 2013; Perez et al , 2016; Hu et al , 2017; Wang et al , 2017; Connolly et al , 2021; Nagy et al , 2021). Thus, Fn14 is intensively tested as a drug target using monoclonal antibodies or immunotoxins targeted to Fn14 or fusion proteins encoding Fn14 decoy receptors, which improve pathology in various mouse models of disease, such as for lung tumors, triple‐negative breast cancer, tumor cachexia, and atherosclerosis (Yepes et al , 2005; Schapira et al , 2009; Michaelson et al , 2011; Wajant, 2013; Zhou et al , 2014; Johnston et al , 2015; Peng et al , 2018; Alvarez de Cienfuegos et al , 2020; Dancy et al , 2020; Wolf et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…38 Our group recently reported that glioblastoma tumor-associated macrophages (TAMs) express Fn14 through analysis of single-cell RNA sequencing data. 27 Fn14 expression has also been detected in human monocyte cell lines, 39 peritoneal macrophages, and peripheral blood mononuclear cells. 40 These findings suggest that Fn14-targeted DART NPs may associate with Fn14-positive non-neoplastic cells in the tumor-immune microenvironment (TIME).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor (TNF)-like weak inducer of apoptosis (TWEAK) and its receptor, fibroblast growth factor-inducible 14 (Fn14), are members of the TNF and TNFR superfamilies, respectively, that are primarily involved in repair processes that occur following tissue injury . Fn14 expression is low in healthy tissues but upregulated in over a dozen solid tumors, including TNBC tumors and metastases, , and high Fn14 levels have been shown to correlate with advanced tumor stage and poor patient outcomes. , Importantly, Fn14 is also significantly overexpressed in BC BMs, where it has been identified as the most useful and accurate predictive biomarker of BM in luminal BC subtypes . The function of Fn14 in primary or metastatic BC is unclear; however, ectopic expression of Fn14 in TNBC cells stimulates cell migration and invasion, suggesting a potential metastasis-promoting function …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive glioma cells are resistant to clinical standard-of-care chemotherapy, along with radiation [ 15 ]. The emerging molecular target implicated in invasive glioma biology is the TNF receptor superfamily member named fibroblast growth factor-inducible 14 (Fn14) [ 5 , 38 ]. Additional, mural-like tumor cells differentiate from GSCs.…”
Section: Resultsmentioning
confidence: 99%